(untitled) (Baghdad Science Journal, 2025)
The study of determing concentration uranium in samples of female teeth. Concentrations of uranium has measured in this study for (10) samples of female teeth distributed on the some of middle and south governorate of Iraq (Muthana – Dekar – Basrah – Najaf – Karbalah – Waset – Babel – Baghdad) . The uranium concentration in teeth samples measured by using fission tracks registration in (CR-39) track detector that caused by the bombardment of (U) with thermal neutrons from (Am-Be) neutron source that has flux of (5x103n.cm-2s-1). The concentrations values were calculated by a compartion with standard samples. The results that the uranium concentrations in female teeth are(0.022) ,(0.038) ,(0.056) , (0.089),(0.15),(0.15),(0.169),(0.17) Pmm respectively. As a conclusion from the study of uranium concentration in Muthana governorate is higher than Dekar and Basrah , Najaf , Karbalah, Waset , Babel and last Baghdad .).